2018
DOI: 10.7181/acfs.2018.00017
|View full text |Cite
|
Sign up to set email alerts
|

Multiple foreign bodies causing an orocutaneous fistula of the cheek

Abstract: Foreign bodies impacted in the maxillofacial region are often a diagnostic challenge. They can be a source of chronic inflammatory reactions and infections leading to the formation of an orocutaneous fistula. Such orocutaneous fistulas cause significant morbidity in most patients, eventually requiring surgery. Recently, we encountered a very rare case of an orocutaneous fistula caused by multiple foreign bodies in the cheek. Precise removal of the foreign bodies was required, and a double-sided anterolateral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Bone fixation is necessary if a fracture is present. Infection control by using appropriate antibiotics is also a key to success [1,2,6,7]. The treatment is complemented by appropriate resuscitative management (e.g., volume replacement and securing the airway) along with an evaluation of bleeding and airway obstruction [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bone fixation is necessary if a fracture is present. Infection control by using appropriate antibiotics is also a key to success [1,2,6,7]. The treatment is complemented by appropriate resuscitative management (e.g., volume replacement and securing the airway) along with an evaluation of bleeding and airway obstruction [2].…”
Section: Discussionmentioning
confidence: 99%
“…Penetrating wounds to the face are cosmetically devastating and life-threatening injuries that often necessitate emergent management [1,2]. X-ray, ultrasonography, and computed tomography (CT) can be used to identify remaining foreign bodies requiring removal, but some foreign bodies may be difficult to detect depending on their type or size [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An orocutaneous fistula is a histopathological pathway from the oral cavity to the facial cutaneous surface. This refractory complication results in eating difficulties [ 19 , 33 , 34 ]. A previous study reported that patients with orocutaneous fistulas responded less to conservative treatment [ 11 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that patients with orocutaneous fistulas responded less to conservative treatment [ 11 , 19 ]. Therefore, surgical intervention is considered effective [ 33 , 34 , 35 ]. In our study, 15 patients experienced this complication, and only surgical treatment was successful in improving their prognoses.…”
Section: Discussionmentioning
confidence: 99%